2007
DOI: 10.1590/s1516-93322007000200010
|View full text |Cite
|
Sign up to set email alerts
|

Atividade antimicrobiana de Senecio heterotrichius DC. (Asteraceae)

Abstract: Neste trabalho é relatada a avaliação da atividade antimicrobiana dos extratos diclorometânico e etanólico, obtidos por maceração das partes aéreas de S. heterotrichius pelo método de microdiluição em caldo, frente a patógenos bacterianos e fúngicos. O extrato diclorometânico evidenciou boa atividade inibitória frente a Candida krusei (CIM de 0,25 mg/mL) e moderada atividade frente a Staphylococcus aureus (CIM de 2,5 mg/mL). O extrato etanólico mostrou-se inativo frente aos microrganismos testados. Também foi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
6
0
2
Order By: Relevance
“…This compound is present in several plant families, including Asteraceae (Mouzuraitis et al, 2002) and is frequently found in Senecio species (Bohlmann & Zdero, 1982b;Bohlmann et al, 1980Bohlmann et al, , 1983Bohlmann et al, , 1985Deuschle, 2003;Deuschle et al, 2007;Francescato et al, 2003;Francescato, 2007;Murari 2007;Jakupovic et al, 1991). As biological activity is to emphasize it's ability to interact with insects and other organisms (Mozuraitis et al, 2002;Rostelien et al, 2000;Stranden et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…This compound is present in several plant families, including Asteraceae (Mouzuraitis et al, 2002) and is frequently found in Senecio species (Bohlmann & Zdero, 1982b;Bohlmann et al, 1980Bohlmann et al, , 1983Bohlmann et al, , 1985Deuschle, 2003;Deuschle et al, 2007;Francescato et al, 2003;Francescato, 2007;Murari 2007;Jakupovic et al, 1991). As biological activity is to emphasize it's ability to interact with insects and other organisms (Mozuraitis et al, 2002;Rostelien et al, 2000;Stranden et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The greater sensitivity of S. aureus is in accordance to literature, which indicates a greater sensitivity of this bacterium to secondary metabolites (Ferreira et al, 2010). The double membrane present in gram-negative bacteria makes up a complex casing, responsible for the lower sensitivity of these microorganisms to plant extracts (Francescato, Deuschle, Mallmann, Alves, & Heinzmann, 2007), as well as lower antifungal activity in natural compounds (Estevez-Braun, Estevez-Reyes, Moujir, Ravelo, & Gonzalez, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…La utilización de plantas pertenecientes al género Senecio como medicinales es debido a la presencia de diferentes clases de metabolitos secundarios, puesto que son ricos en monoterpenoides, sesquiterpenoides, flavonoides, entre otros. Por otro lado, las actividades biológicas comprobadas para estas especies son variadas, tales como, propiedades insecticidas, actividades antimicrobiana, citotóxica, antiviral y antioxidante (Francescato et al, 2007) y el aceite esencial derivado de sus diferentes órganos (hojas, tallos y flores) presentan variaciones en su composición química. S. graveolens Wedd, conocida como "chachacoma", crece como arbusto en el sur de Brasil, y en los andes de Argentina, Chile y Perú.…”
Section: Tablaunclassified